INVESTIGATING THE USE OF DEIXIS “PEOPLE, PLACE AND TIME” IN JAKARTA POST - DESTI Hera Wati (Journal of English Education, Literature and Linguistics, 2020)
Problem of this research was “what are the uses of deixis “people, place, and time” in Jakarta Post?”. Objective of this research is to find out and analyze by describing the forms of deixis used Jakarta Post. Method of collecting the data was used descriptive qualitative research. Instruments of collecting data were collected by human instrument and text analysis. Technique in collecting the data,researcher read, identified, and classified the deixis use in Jakarta Post (only City column). Based on the result of data analysis, it was found that the pronoun deixis of Person was often used as second person, third person, possessive personal plural person, and reflective personal person. In addition it was found that the deixis of the time, was often adverb of time like since, years ago, next month, last years, and so on. Moreover, the deixis of a place was also found that adverb of place such as here, there and etc.Therefore, it can be concluded that researcher found the all kinds of deixis “people, place, and time” in Jakarta Post.